Средневековая усадьба XIII в. в Северном районе Херсонеса (постоялый двор) - Рыжов, С. Г. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARYRizhov S.G. A Middle — Aged Farmstead of the XIII century in the Northern Region of Chersonesus (A Coaching Inn)The article is devoted to one of the principle problems of building Chersones in X - XIII centuries. On the basis of analysis of building and archeological materials, got during the excavations, the planned building of one of the regions in presented and the graphic reconstructions of the country estate of the XIII century is given. Basing on the building remains, the author comes to the conclusion that the country estate used to be a coaching inn. For defining its belonging to some period, the archeological materials got during the excavations of the country estate itself and the adjoining plots were used.